2020
DOI: 10.3389/fmars.2020.543829
|View full text |Cite
|
Sign up to set email alerts
|

Anthropozoonotic Parasites Circulating in Synanthropic and Pacific Colonies of South American Sea Lions (Otaria flavescens): Non-invasive Techniques Data and a Review of the Literature

Abstract: Parasitic Infections in Sea Lions present study illustrates a successful application of non-invasive screening methods and their applicability in the field of marine mammal parasitology, bringing new insights into the endogenous parasite fauna of South American sea lions in Southern Chile, including anthropozoonotic protozoan and metazoan taxa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 80 publications
0
7
0
1
Order By: Relevance
“…Measurements in micrometers, unless otherwise stated Species D. sprakeri n. sp. D. sprakeri n. sp.1 a D. scoticum c D. scoticum d Host Zalophus californianus (Lesson) Otaria flavescens Shaw Hydrurga leptonyx (Blainville) H. leptonyx Locality California, USA Los Lagos Region, Chile Antarctica Antarctica GenBank accession no MW600337–MW600339 ( lsr DNA); MW596661, MW596666–MW596673, MW596675–MW596678, MW596680 ( cox 1) KY945917 ( lsr DNA); KY945922, MF893274 ( cox 1) Reference Present study Hermosilla et al [ 24 , 25 ] Rennie and Reid [ 42 ] Fuhrmann [ 43 ] d Strobila length (cm) < 200 × 0.8 > 50 13.3–29 13.3 Scolex 999–1484 × 807–1275 1800–2500 × 1500 1800–3000 × 700–2500 Neck Absent Short Absent Gravid proglottid (cm) 0.03–0.07 × 0.27–0.79 0.08–0.14 × 0.71–0.74 0.09 × 0.15 0.12 × 0.55 Testes diameter or size 44–70 150 b ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements in micrometers, unless otherwise stated Species D. sprakeri n. sp. D. sprakeri n. sp.1 a D. scoticum c D. scoticum d Host Zalophus californianus (Lesson) Otaria flavescens Shaw Hydrurga leptonyx (Blainville) H. leptonyx Locality California, USA Los Lagos Region, Chile Antarctica Antarctica GenBank accession no MW600337–MW600339 ( lsr DNA); MW596661, MW596666–MW596673, MW596675–MW596678, MW596680 ( cox 1) KY945917 ( lsr DNA); KY945922, MF893274 ( cox 1) Reference Present study Hermosilla et al [ 24 , 25 ] Rennie and Reid [ 42 ] Fuhrmann [ 43 ] d Strobila length (cm) < 200 × 0.8 > 50 13.3–29 13.3 Scolex 999–1484 × 807–1275 1800–2500 × 1500 1800–3000 × 700–2500 Neck Absent Short Absent Gravid proglottid (cm) 0.03–0.07 × 0.27–0.79 0.08–0.14 × 0.71–0.74 0.09 × 0.15 0.12 × 0.55 Testes diameter or size 44–70 150 b ...…”
Section: Resultsmentioning
confidence: 99%
“…Hermosilla et al [ 24 ] reported a ‘ Diphyllobothrium scoticum -like cestode’ from SASLs from the Pacific coast of Chile to be molecularly conspecific with samples from CSLs. The recent revision of metazoan parasites of SASL by Ebmer et al [ 25 ] reported 44 metazoan taxa (only 25 were identified to the species level), including A. pacificus with its synonyms, Clistobothrium delphini (Bosc, 1802) [as Phyllobothrium delphini (Bosc, 1802)] and unidentified species of Anophryocephalus Baylis, 1922 and ' Diphyllobothrium '.…”
Section: Introductionmentioning
confidence: 99%
“…En este sentido, se incentiva una conducta de acostumbramiento del león marino debido a que en ese lugar puede acceder fácilmente a una fuente de alimento alternativo, situación también registrada en la Feria Fluvial de Valdivia con una serie de implicancias negativas tanto para el león marino como para el ser humano (Root-Bernstein et al 2012, Sepúlveda et al 2015. Por ello, se recomienda evaluar la interacción que aquí se está estableciendo entre los LMC y las pescaderías en virtud de los efectos negativos, la posible dependencia trófica a los desperdicios de la pesca que aquí son entregados, y a la potencial fuente de transmisión de enfermedades zoonóticas entre leones marinos y humanos, como lo ya descrito para otra localidad (i.e., Sepúlveda et al 2015, Hermosilla et al 2016, Ebmer et al 2020.…”
Section: Cetáceos Avistados Desde Plataforma Terrestreunclassified
“…Helminth nematodes of the family Anisakidae have a worldwide distribution and present a complex heteroxenous lifecycle in marine habitats including various intermediate host species (Koie et al 1995). Several anisakid nematodes have been found as adult stages parasitizing the digestive tract of marine mammals including seals, sea lions, sea leopards, sea elephants, baleen, and toothed cetaceans (Hermosilla et al 2016;Mattiucci et al 2018;Ebmer et al 2020). Conversely to adult stages, anisakid larval stages are often found parasitizing the body cavity and muscle of many obligate intermediate/paratenic host fish species and cephalopods (Chai et al 2005;Mattiucci et al 2018).…”
Section: Introductionmentioning
confidence: 99%